Penguatan Pendidikan Agama Islam Melalui Pendekatan Humanis Untuk Mengembangkan Karakter Religius Peserta Didik di Sekolah: Strengthening Islamic Religious Education Through a Humanistic Approach to Develop the Religious Character of Students in Schools - Mochammad Salman Alfarisi; Moh Ilham Maulana Romzi; M Mahbubi (Qudwah: Journal of Islamic Education, 2026)
This article discusses the strengthening of Islamic Religious Education (PAI) through a humanisticapproach as a strategic effort to shape students’ religious character in schools. The humanisticapproach positions students as active subjects who possess potential, needs, and experiences that mustbe respected in the learning process. In the context of modern education—which demands moredialogical, empathetic, and student-centered learning—PAI is required to present methods that notonly emphasize cognitive aspects but also foster a deep internalization of religious values. Using adescriptive qualitative method with a literature study, this article analyzes the concept of thehumanistic approach, its implementation strategies in PAI learning, and its relevance to thedevelopment of religious character. The findings show that the humanistic approach creates a moreopen, communicative, and inclusive learning environment that values students’ diverse abilities,thereby facilitating the internalization of Islamic teachings. Teachers act as facilitators who encouragereflection, dialogue, and role modeling in daily behavior, allowing values such as honesty,responsibility, empathy, discipline, and noble character to be naturally instilled. Thus, the humanisticapproach proves to be relevant and effective in strengthening Islamic Religious Education and formingstudents who are not only intellectually intelligent but also spiritually and morally mature.